Benign metastasising leiomyoma presenting with respiratory distress. Issue 7 (8th October 2019) - Stabler, Robert; Azim, Adnan; Edwards, Dawn
Abstract : Benign metastasising leiomyoma (BML) is a rare gynaecological tumour which most commonly presents with incidental lung nodules. Here, we present a case of BML in which a 43-year-old woman was admitted in respiratory distress. She was found to have widespread lung involvement with numerous, moderately sized lesions and emphysematous lung regions. Imaging of this patient demonstrated more extensive respiratory disease than has previously been reported in BML, and rendered surgical resection of the nodules impossible. We describe the patient's treatment with chemical castration and report some improvement in both lung imaging and function.